Farmers’- led extension: Contexts, experiences and way forward - Das, Usha; Ghosh, Souvik (Indian Farming, 2019)
The current phase of agricultural development aims at greater inclusiveness and equitable transformation, whereby farmers are able to reap economic benefits. The doubling farmers’ income (DFI) Committee is guided by the fact that more than 85% of the farm holdings are small and marginal, and are economically challenged. To achieve income growth, there is a need for deploying scales of operation, and therefore, the need for promoting new generation farmer collectives, such as Commodity Interest Groups (CIGs), Farmer Producers Organisations (FPOs) – both as Cooperatives and Companies and Village Produce Organisations (VPOs). Farmers’ led extension approach has been successful in different parts of the country and complement public led agricultural extension for improving farm income and livelihood.